2003
DOI: 10.1021/je025566c
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium for Phenol + α-Methyl Benzyl Alcohol and 2-Ethoxyethanol + n-Butyl Formate

Abstract: The saturation pressure of α-methyl benzyl alcohol (358 to 398) K and n-butyl formate (313 to 359) K was measured by an ebulliometric method. The vapor−liquid equilibrium (p, T, x, y) at (353.15, 373.15, and 393.15) K was measured by the ebulliometric method for the systems phenol + α-methyl benzyl alcohol and at (333.15, 343.15, and 353.15) K for 2-ethoxyethanol + n-butyl formate. The experimental vapor pressures were correlated with the Antoine and AEOS equations, whereas VLE was correlated with AEOS equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Ebulliometric VLE measurements of mixtures containing 2-ethoxyethanol (including the pure components) were performed by Malanowski and coworkers. , This data is quite consistent with our static measurements. Otherwise, only vapor pressure data with unreasonable trends from the same studies that were excluded in the case of 2-methoxyethanol and single-point data from VLE studies were found in the literature.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Ebulliometric VLE measurements of mixtures containing 2-ethoxyethanol (including the pure components) were performed by Malanowski and coworkers. , This data is quite consistent with our static measurements. Otherwise, only vapor pressure data with unreasonable trends from the same studies that were excluded in the case of 2-methoxyethanol and single-point data from VLE studies were found in the literature.…”
Section: Resultssupporting
confidence: 90%
“…Brown circles, Pick et al; forest green inverted triangles, Antosik et al; blue diamonds, Chylinski et al; red hexagonal stars, Antosik et al; green left-pointing triangles, DeBord et al; navy stars, Alderson et al. ; purple triangles, Chylinski et al; magenta right-pointing triangles, Pathare et al. ; forest green cross marks, Lladosa et al; brown plus signs, Cortinovis et al (partially displayed); orange open squares, Rana et al; olive asterisks, Reddy et al (partially displayed); red solid squares, this work (static); dotted lines, absolute deviations.…”
Section: Resultsmentioning
confidence: 99%
“…The vapor pressure data were compared with those of Dreisbach and Shrader 10 and earlier investigations from our laboratory. 11 The comparison is given in Figure 5. The results are satisfactory.…”
Section: Correlationmentioning
confidence: 99%
“…For water, the parameters calculated by NIST from Bridgeman and Aldrich data 8 were used. The vapor pressure data were compared with those of Dreisbach and Shrader 10 and earlier investigations from our laboratory . The comparison is given in Figure .…”
Section: Correlationmentioning
confidence: 99%